2018
DOI: 10.1111/gean.12172
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Location of Rescue Ambulance Dispatch Bases: A Case Study in Rio de Janeiro, Brazil

Abstract: Emergency Medical Services are considered critical elements of modern health services, to assure the appropriate level of service to the population. We applied the facility location theory to indicate strategic points to establish ambulance dispatch centers to attend emergency calls. Therefore, the main objective of this paper is to promote an analysis of the locations of rescue ambulance bases in the city of Rio de Janeiro, focusing on reducing the response time of calls. We propose a mathematical model which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Their analysis found that proper placement of the rescue source point could increase the effectiveness of rail accident rescue and the demand for urban medical services. Ferrari et al 17 also developed a multi-objective model for locating EMS centers to maximize the number of service delivery and demand coverage and minimize the number of facilities and the distance between them. In that research, the calls for EMS and the population at demand points were integrated into a network of demands.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their analysis found that proper placement of the rescue source point could increase the effectiveness of rail accident rescue and the demand for urban medical services. Ferrari et al 17 also developed a multi-objective model for locating EMS centers to maximize the number of service delivery and demand coverage and minimize the number of facilities and the distance between them. In that research, the calls for EMS and the population at demand points were integrated into a network of demands.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A multi-objective approach for an EMS is addressed by Ferrari et al (2018) which propose a multi-objective formulation considering five objectives: maximizing the covered population, maximizing the number of demand points covered, minimizing the number of stations to be installed, minimizing the distance between demand points and stations, and also minimize the penalization for the demand that can not be allocated to any bases due to capacity restrictions.…”
Section: Bi-objective Problemmentioning
confidence: 99%
“…The availability of rich real-world data from these organizations has provided opportunities to improve various aspects of medical emergency response [5][6][7]. Several studies have been done to this end, falling under several research scopes, such as ambulance dispatch planning [8,9], station and ambulance placement and relocation [10,11], vehicle routing [12,13], hospital evacuation [14,15], and visualization/decision support [16,17]. However, in addition to these contributions, there is also a need to assess existing emergency response systems, unraveling patterns that highlight potential local problems in those systems.…”
Section: Introductionmentioning
confidence: 99%